Perilaku Menyikat Gigi Penderita Diabetes Mellitus Sebelum Dan Sesudah Diberikan Penyuluhan Dengan Media Flipchart di Puskesmas - Giri, Ni Kadek Septhia Dwi Kusuma; Dwiastuti, Sagung Agung Putri (Jurnal Kesehatan Gigi (Dental Health Journal), 2026)
Diabetes mellitus can cause oral health problems, such as dry mouth, bleeding gums, and other dental health problems due to decreased saliva flow, which increases the risk of infection and bacterial growth. Prevention through good brushing habits is very important, and health education using flipcharts can be an effective educational method. This study aims to determine the toothbrushing behavior of patients with diabetes mellitus before and after receiving education using flipchart media. The research design used is descriptive with an observational approach. The research population is all patients who visit the health center, and the sample is taken using accidental sampling. Data are collected through observation sheets and analyzed univariately in the form of frequency distribution and mean values. The results showed that before counseling, most respondents had adequate toothbrushing behavior (78.9%) with an average score of 65, while after counseling, the majority of respondents had good behavior (94.7%) with an average score of 89.7. Counseling using flipcharts proved to be effective in improving toothbrushing behavior in patients with diabetes mellitus.